Empowerment of Gulf Communities Tomini In Improving Blue Economy Through Soft skills Technopreneurship in the Subdistrict North Leato, Gorontalo - Lapananda, Eva Rivana; Pomalingo, Samsi; Nurain,; Pontoh, Riviyanti; Tala'a, Rahmat; Alhijrah,; Ajengsari, Desti; Patamani, Tri Yulianti; Tupamahu, Jessia Ruth Cladya; Nabius, Riski (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This research discusses the processing of skipjack tuna into frozen food in the form of rolls for UKM (Small and Medium Enterprises) groups in the North Leato sub-district, Gorontalo City. The study aims to improve the understanding of UKM groups regarding skipjack tuna processing to enhance the blue economy through technopreneurship soft skills training. Method: The process of making skipjack tuna rolls began with coordination with the UKM group members. This was followed by a socialization session about community empowerment in producing long-lasting fish products. After the socialization, training was conducted on processing skipjack tuna and utilizing fish waste as organic fertilizer. This was done to assess the participants’ understanding of processing skipjack tuna into rolls. A Focus Group Discussion (FGD) was then held with the community and the North Leato government to discuss marketing techniques and product processing. Practical Application: The results offer practical benefits for the SME groups in the North Leato sub-district by increasing their understanding of skipjack tuna processing training, which can help improve their income and ensure sustainability in producing skipjack tuna rolls. Conclusion: Empowering the community around Tomini Bay, especially in the North Leato sub-district, is a strategic step in enhancing the blue economy through the development of technopreneurship soft skills. Through training and interpersonal skill development, the community can become better prepared to manage marine resources sustainably and foster creative innovation in technology-based businesses.